IMPROVING STUDENTSâ€™ READING COMPREHENSION OF DESCRIPTIVE TEXTS USING COLLABORATIVE STRATEGIC READING TECHNIQUE - Ningsih, Winarti Ayu; Sudarsono, Sudarsono; Rosnija, Eni (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe present research was an attempt to systematically investigate the improvement of teaching collaborative strategic reading (CSR) technique on studentsâ€™ reading comprehension of descriptive texts in Year-8 of â€œSMP Negeri 18 Pontianakâ€ in the academic year of 2016/2017. The research was a classroom action research which consisted of planning, acting, observing, and reflecting. It was done in three cycles. The subject of the research was Learning Group VIIID with 35 students. The data were collected by an observation and measurement technique. The tools were observation checklist, field note and reading test to observe the studentsâ€™ behaviors in the classroom. The result showed that the students could comprehend a descriptive text because the teaching and learning behaviors were improved. The improvement of the behavior of students and teacher in the classroom affected the improvement of studentsâ€™ skill in reading. Sharing in group discussion made studentsâ€™ social skill getting better and more active in the classroom. Therefore, the studentsâ€™ achievement was improved significantly. As a conclusion, the problems that the students faced could be solved through group discussion using CSR technique.Â Keywords: Collaborative Strategic Reading, Reading Comprehension, Descriptive TextÂ Â Â Â Â Â Â Â Â